2012
DOI: 10.1007/s11682-012-9173-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of mild traumatic brain injury (mTBI): progress and perspectives from the first decade of studies

Abstract: Mild traumatic brain injury (mTBI) represents the great majority of traumatic brain injuries, and is a common medical problem affecting cognitive and vocational functioning as well as quality of life in some individuals. Functional MRI (fMRI) is an important research method for investigating the neuroanatomic substrates of cognitive disorders and their treatment. Surprisingly, however, relatively little research has utilized fMRI to examine alterations in brain functioning after mTBI. This article provides a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 53 publications
1
88
2
Order By: Relevance
“…1,3,6 Standard clinical neuroimaging sequences (computed tomography [CT] scans; T1 and T2-weighted images), however, are typically negative for the majority of patients, leading to a proliferation of studies that have attempted to define objective biomarkers of mTBI. 7 There has been great interest in using functional magnetic resonance imaging (fMRI) to study mTBI given the ability to perform in vivo measurements of neuronal function during demanding cognitive tasks 8 as well as during passive mental activity. [9][10][11] Previous fMRI studies have reported a mixed pattern of both hypoand hyperactivation during the semi-acute stage of mTBI, as well as no observable group differences.…”
mentioning
confidence: 99%
“…1,3,6 Standard clinical neuroimaging sequences (computed tomography [CT] scans; T1 and T2-weighted images), however, are typically negative for the majority of patients, leading to a proliferation of studies that have attempted to define objective biomarkers of mTBI. 7 There has been great interest in using functional magnetic resonance imaging (fMRI) to study mTBI given the ability to perform in vivo measurements of neuronal function during demanding cognitive tasks 8 as well as during passive mental activity. [9][10][11] Previous fMRI studies have reported a mixed pattern of both hypoand hyperactivation during the semi-acute stage of mTBI, as well as no observable group differences.…”
mentioning
confidence: 99%
“…Functional MRI and ERPs have been found to be among the most sensitive of these techniques (for recent reviews see Gosselin and colleagues 25 and McDonald and colleagues 37 ). One advantage of these approaches is that they allow the measurement of brain function during the performance of a cognitive task.…”
mentioning
confidence: 99%
“…An initial 69 PCS patients underwent the fNCI protocol and z-scores were calculated for each FR in each fNCI exam. In previous task-related fMRI studies of PCS, distinct patterns of either hyperactivation [25][26][27][28][29][30][31][32] or hypoactivation [26,[33][34][35][36][37][38][39][40] have been reliably observed, depending on the cognitive task employed and the cortical…”
Section: Biomarker Candidate Searchmentioning
confidence: 99%